Security Challenges and Approaches in Internet of Things - Misra, Sridipta; Maheswaran, Muthucumaru; Hashmi, Salman; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive survey of the security and privacy research advancements in Internet of Things (IoT). The book lays the context for the discussion by introducing a system model for IoT. Since IoT is very varied and has been introduced in many different contexts, the system model introduced plays a crucial role in integrating the concepts into a coherent framework. After the system model, the book introduces the vulnerable features of the IoT. By providing a comprehensive discussion of the vulnerable features, the book highlights the problem areas of IoT that should be studied concerning security and privacy. Using the vulnerable features as a motivation, the book presents a vast survey of existing security and privacy approaches for IoT. The survey is a good way for the reader to pick up interesting directions of research that have already been explored and also hints at directions that could take additional investigation. Finally, the book presents four case studiesthat provide a detailed view of how some of the security and privacy concerns are addressed in specific problem areas.
Introduction -- Motivation -- System Model for the Internet of Things -- Vulnerable Features and Threats -- Securing the Internet of Things -- Security Approaches in Internet of Things -- Conclusion.
Keywords: Telecommunication; Application software; Signal processing; Data protection; Communications Engineering, Networks; Computer and Information Systems Applications; Signal, Speech and Image Processing; Data and Information Security